Evaluación de la efectividad del aceite esencial del árbol de té (Melaleuca alternifolia) frente tres géneros bacterianos aisladas de mastitis bovina - Veloz Carrasco, Sahara Belén (2023)
Bovine mastitis is one of the diseases with the greatest negative impact on the dairy industry worldwide since it is considered to be the main cause of the spread of multiresistant bacteria. The objective of this research was to evaluate the antimicrobial effectiveness of tea tree essential oil (Melaleuca alternifolia) against three bacterial genera isolated from bovine mastitis. Methodologically, the essential oil was obtained by steam distillation, the antimicrobial activity was evaluated by the disc diffusion method of the essential oil at concentrations of 75%, 50%, 30%, 20% and 10%, against Escherichia coli, Klebsiella spp, and Staphylococcus aureus, which were isolated and identified from previously conducted research. In addition, the identification of volatile compounds was performed by gas chromatography-mass spectrometry (GC-MS), using a HP5-MS column. As a result, it was obtained that from an average of 154 g of leaves, 3.28 mL of essential oil was distilled, with a yield of 2.12%, that is, for every 100 g of tea tree leaf, 2.12 mL of essential oil will be obtained, within the antibiogram study there were highly significant statistical differences (p<0. 05) in the measurements of the inhibition halos at the concentrations proposed, while at the level of repetitions no significant differences were evidenced, that is to say that the 10 isolates under study behaved in a similar way, in addition to inhibit in their totality the bacterial population of Escherichia coli, Klebsiella spp, and Staphylococcus aureus in the study required a concentration of tea tree essential oil at 50%, 20% and 10%, respectively. Chromatographically, it was evidenced that L-terpinen-4-ol was the predominant compound with an area of 34.02% in relation to the other volatile compounds, to which the antimicrobial activity is attributed. It was concluded that a minimum concentration of 50% of tea tree essential oil is necessary to completely inhibit the bacteria causing bovine mastitis.